2021
DOI: 10.1136/bmj.n2098
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19: 40% of patients with weakened immune system mount lower response to vaccines

Abstract: Four in 10 people who are clinically vulnerable generate lower levels of antibodies than healthy recipients after two shots of vaccine against SARS-CoV-2, a study has found. 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 2 publications
1
6
0
Order By: Relevance
“…Such a deficiency is usually expected from immunocompromised/ multiple sclerosis patients with impaired B cells mounting. 12,16 Compared to females, diminished virusneutralizing antibody production in males is in the line with a previous study highlighting suppressive impacts of testosterone on postvaccination IgG against Omicron variant; so, it is based on hormonal differentiation. 5,6,7,10,17 Greater than normal BMI hampers the vaccination-elicited response 10,18 through intrinsic immunological perturbations.…”
Section: Discussionsupporting
confidence: 87%
“…Such a deficiency is usually expected from immunocompromised/ multiple sclerosis patients with impaired B cells mounting. 12,16 Compared to females, diminished virusneutralizing antibody production in males is in the line with a previous study highlighting suppressive impacts of testosterone on postvaccination IgG against Omicron variant; so, it is based on hormonal differentiation. 5,6,7,10,17 Greater than normal BMI hampers the vaccination-elicited response 10,18 through intrinsic immunological perturbations.…”
Section: Discussionsupporting
confidence: 87%
“…Vaccination is more beneficial for patients with comorbidities and immunocompromised patients. 83 Studies have shown that vaccinated patients have lower levels of autoimmune IG receptor antibodies and ACE2 receptor antibodies in transplant patients, kidney disease, malignancies, and autoimmune diseases, so they are more susceptible to infection. 84 In our study, fever and cough, typical symptoms of COVID-19 patients, were lower in the vaccine group.…”
Section: Discussionmentioning
confidence: 99%
“…The anti-Covid vaccines that are currently in use weaken the link between cases and hospitalization/deaths [ 41 ]. These vaccines are particularly beneficial for vulnerable individuals who have comorbidities or have weakened immunity [ 42 ]. However, efforts should continue to develop the next generation of vaccines that are preventive in nature and can better confront emerging variants.…”
Section: Developing Next-generation Vaccinesmentioning
confidence: 99%